Actual Problems of Sustainable Development and their Solution in Russia - E. Yu. Kochemasova (Мир новой экономики, 2020)
In the post-industrial period, which began in developed countries in the 1970s–1980s, the processes of globalization and competition in world markets came to the fore. As a result of the intensive development of industry and the growth of domestic consumption, many countries have largely exhausted the economic capacity of their territories. They are experiencing a shortage of raw materials. Over the past sixty years, the world’s leading countries have been implementing a socio-ecological and economic model of social development, which allows them to use financial, labour and natural resources rationally. Russia’s transition to sustainable development can give an additional impetus to the country’s socio-economic development. It also ensures breakthrough scientific and technological progress, increases the competitiveness of the national economy, creates other opportunities for more effective implementation of strategic planning documents and national projects.